Investigating Patterns of Research Collaboration and Citations in Science and Technology: A Case of Chiang Mai University - Boontarika Paphawasit; Ratapol Wudhikarn (Administrative Sciences, 2022)
This study investigates 3883 articles published by researchers affiliated with Chiang Mai University in science and technology from January 2010 to December 2019 to test whether research team characteristics and collaboration patterns can determine a citation rate. Citations were retrieved from the Scopus database and compared with their (1) number of authors, (2) type of publication, (3) gender of authors, (4) SJR values, (5) country of international collaborators, (6) number of affiliated institutions, and (7) international diversity index. The findings were based on quantile regressions and indicated that the number of authors strongly influenced citations, which increases the likelihood of being cited. The citation advantage of being a foreign-first author only existed at the 0.25th quantile; however, the evidence of foreign-first author citation advantages or disadvantages for the moderate and very productive publications was not found. A significantly positive effect of SJR value on citations was found while being a female first author negatively impacted the citation rate. These findings can be used in the planning and managing process of producing scientific and technological research to improve the research quality, boost the research impact, and increase opportunities for research results to be utilized.